واقع ممارسة الأنشطة اللاصفية من وجهة نظر مُشرفي النشاط المدرسي (مدارس التعليم الأساسي بمدينة بنغازي نموذجاً) - حامد المبروك صالح (Scientific Journal of University of Benghazi, 2019)
The study aimed to identify the reality of the practice of extra-curricular activities in basic education and its nature, concept, importance and objectives, and to identify the extent to which supervisors and specialists are aware of the importance of extracurricular activities and identify the most important extracurricular activities. In Benghazi city and identify the most important obstacles and difficulties encountered by supervisors and specialists in the activity in the implementation of extra-curricular activities. The researchers used the descriptive approach. The study sample consisted of (91) teachers and teachers with 27% A questionnaire consisting of (66) words distributed in three areas. The Alpha Kronbach coefficient, the arithmetic mean, the standard deviations and the relative weights were used. The study showed that the respondents are very aware of the importance of extracurricular activities. Social _ school concerts _ drawing _ music, singing and singing _ handball _ football _) and the most important constraints of extra-curricular activities (lack of some of the material resources available to practice activities, weak budgets approved for educational activities _ The study adopted several recommendations, the most important of which are: To provide the appropriate financial budgets and financial resources from playgrounds, theaters, workshops, lounges, equipment and tools. Providing material and moral incentives for supervisors of extracurricular activities as well as providing appropriate incentives for students, which encourage them to practice activities, and work to diversify the activity of non-school, and increase the focus and attention to Stom school activities and determine the appropriate times to them, and work to rehabilitate and refine activity teachers through training courses